Late-onset renal variant Fabry disease with R112H mutation and mild increase in plasma globotriaosylsphingosine: a case report - Tanaka, Keiko; Sugiyama, Hitoshi; Morinaga, Hiroshi; Onishi, Akifumi; Tanabe, Katsuyuki; Uchida, Haruhito A.; Maruyama, Hiroki; Wada, Jun (Frontiers in Medicine, 2024)
Fabry disease (FD) is an X-linked disorder resulting in a deficiency of α-galactosidase A (GLA) activity. The R112H mutation of GLA is relatively common in Japanese FD patients, characterized by a late-onset phenotype, almost normal to mild lyso-Gb3 elevation, and mild clinical symptoms, despite low GLA activity. This is due to the structural features of the R112H GLA protein. We herein report the case of a 42-year-old male patient with late-onset FD with a R112H mutation. The patient exhibited only renal involvement with no other organ damage and was successfully treated with galactosidase beta and subsequent migalastat for approximately 10 years. Especially, migalastat was clinically effective in normalizing plasma lyso-Gb3 levels and inhibiting the progression of renal damage associated with FD. Therefore, the use of migalastat in the FD patients with R112H mutation is highly recommended based on this case report.